Virtual Manipulatives with Integrated Sign Language: Digital Innovation in Mathematics Learning for Deaf-Mute Students in Inclusive Elementary School - Antara, I Gede Wahyu Suwela; Suarjana, I Made; Simamora, Alexander Hamonangan; Deng, Jian Bang (DPPM Universitas Pelita Bangsa, 2025)
This study aims to examine the validity of sign language-based virtual manipulatives media for teaching mathematics to deaf-mute students in inclusive elementary schools. The research employed a Research and Development (R&D) method using the ADDIE development model. Validation was conducted by three categories of experts: media expert, inclusive instructional design expert, and mathematics content expert. The instrument used was a validation sheet featuring a Likert scale and a qualitative feedback column. The validation results showed that the media achieved an average score of 94.73%, placing it in the